Ethical Issues Regarding Dermatopathology Care for Service-Members: A Review - Samir Kamat; Ross O’Hagan; Catherine Brahe; Curtis L. Hardy; Vikas Shrivastava; Jane M. Grant-Kels; Angela M. Crotty (Dermatopathology)
Dermatologic care within the military faces unique ethical challenges. Service members are stationed across nationally and globally diverse settings, and therefore, dermatologic care rendered ranges from within resource-rich, advanced military medical treatment facilities to austere, resource-limited, deployed field environments. Additionally, military service members are often at unique risk for dermatologic disease, given occupational, environmental, and geographic exposures not commonly faced by their civilian counterparts. This review explores topics in dermatoethics via case analyses of ethical considerations within the scope of dermatologic care for military service members.